Adequação da demanda hídrica e da potência instalada em sistemas de recalque para o arroz na depressão central do Rio Grande do Sul. - Corrêa, Henrique Cunha (2007)
The rice culture for Rio Grande do Sul economy is of great relevance. Annually, around one million of hectares are planted. As it is a culture irrigated by a continuum flood, the supply of the high hydric demand is done in 70% of the area through pumping station, representing a significant portion of the production costs. Associate with this fact, there is a necessity in reducing water and energy consumption, object of several official and private actions undertaken in the latest years with the object of preserving the sources, reducing costs and contouring conflicts in the water access. The objective of this work was to find an easily and quickly way of planning, trying to help the extensions of the pumping station to rice irrigation. Real known data were used related to the ground-plant-climate system of the Central Depression rice culture region, doing a calculation based in the simplified hydric balance adapted to the rice farming system. Instantaneous hydric demands were calculated for the initial flood and for the maintenance of the flood until the end of the irrigation cicle. To reduce either outflows or installed powers was adopted a division of the total areas established in the simulation (between 10 and 190 ha), and after was done a temporal stagger of the sowing and the irrigation process. A reduction of 64% in the outflow of the initial flow was attained and 63% in the installed electrical powers of the pumping station, when compared to the simultaneous flow process of the farming total areas. When it was used the regression analysis, were got equations for outflows adjustment and required power in operation of total areas for estimations in the intervals of the adopted areas in the work. The resource makes possible the previous planning of farmings relating to the instantaneous demand for initial flow and support supply, as well as in relation to the electrical powers, observing pumping stations in installations in parallel (two or more pump motor system) sets. Another possible application refers to the procedures of elaborating Basin Administrative Committees and corresponding processes of warranting right of water use, in order to offer basic and trustful information to establish maximum cultivable areas because of the minimum availabilities established regionally to the activity.